2013
DOI: 10.1108/09590551311306255
|View full text |Cite
|
Sign up to set email alerts
|

The effects of purchase orientations on perceived loyalty programmes' benefits and loyalty

Abstract: International audiencePurpose - This article aims to dwell on theoretical, managerial, and empirical knowledge to improve loyalty programme efficiency. Its intention is to try to understand how economic, hedonist, relational, convenience, informational rewards enhance or undermine customers' perceived programme benefits as well as subsequently loyalty according to individual shopping orientations (economical, hedonist, social-relational, apathetic, brand/loyal). Design/methodology/approach - The research uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 66 publications
(106 reference statements)
1
24
0
2
Order By: Relevance
“…This research result supported also with research conducted by Meyer et, al, (2013) found that the act of purchasing by the consumer into focus institutions could perceived level benefits and loyalty that varies according to the orientation purchase done by consumers. Then research findings pertaining to loyality consumers aircraft according to Anuwichanont (2011) brand trust decisively predict second attitudes and behavior loyality significantly.…”
Section: Figure 2 the Higher Education Institutions Postgraduate Dissupporting
confidence: 87%
“…This research result supported also with research conducted by Meyer et, al, (2013) found that the act of purchasing by the consumer into focus institutions could perceived level benefits and loyalty that varies according to the orientation purchase done by consumers. Then research findings pertaining to loyality consumers aircraft according to Anuwichanont (2011) brand trust decisively predict second attitudes and behavior loyality significantly.…”
Section: Figure 2 the Higher Education Institutions Postgraduate Dissupporting
confidence: 87%
“…Although a customer is sometimes not pleased with financial benefits the retailer offers, he will not opt for a competing program, because his connection to the retailer is above those rewards. "Customers with a strong connection to a company are immune to negative comments which may arrive from competition or other members of the program 25 . Opposite from false loyalty is hidden loyalty which is evident in the positive attitude and customers' opinions, despite rare purchases.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, the application of relational marketing in commercial distribution activities may involve some advantages, such as an increase in consumer loyalty, obtaining benefits for service users, and the promotion of product sales or complementary services. Following this line, Gwinner et al (1998) show that consumers who are motivated and maintain long-term relationships with their service providers do not only expect to receive adequate service but also hope to receive additional benefits (confidence, social, and special treatment), known in the academic literature as relational benefits (Bendapudi & Berry, 1997;Dwyer, Schurr, & Oh, 1997;Reynolds & Beatty, 1999), or benefits derived from a loyalty programme that can take the form of economic, hedonistic, relational or convenience advantages or informational rewards (Meyer-Waarden, Benavent, & Castéran, 2013).…”
Section: Relational Marketingmentioning
confidence: 99%